A CB[5] analogue based supramolecular polymer with AIE behaviors. (26th April 2018) - Wu, Yufan; Hua, Haojie; Wang, Qiaochun
Abstract : An emissive supramolecular polymer was constructed by the self-assembly between a TPE quaternary ammonium salt and a cucurbit[5]uril analogue. Abstract : A supramolecular polymer has been successfully constructed by the self-assembly between a TPE derivative and a cucurbit[5]uril analogue—CyP5 TD[5], through portal interactions. Various characterization methods were adopted to prove the formation of the polymer, such as 1 H NMR, ITC, TEM and 2D DOSY 1 H NMR. In addition, supramolecular polymers exhibit a strong fluorescence in aqueous solution because of their aggregation-induced emission.